Development of the educational system: European vector – 2024 - Онищенко, Сергій Вікторович; Жигірь, Вікторія Іванівна; Бєлова-Олейник, Юлія Юріївна; Мельник, Сергій Володимирович; Бутенко, Дар’я Олександрівна; Морозов, Олег Вікторович; Лавриненко, Лариса Василівна; Масюк, Георгій Ігорович; Титаренко, Людмила Іванівна; Урмич, Олена Михайлівна; Шалупня, Євгеній Олегович; Бабаліч, Вікторія Анатоліївна; et al. (DEL c.z., 2024)
The collection includes materials of the V International research and practical internet conference "Development of the educational system: European vector". The materials of the collection will be useful for researchers, scientists, graduate students, researchers, teachers, students.